Multiplicities of (Il)literacy : An introduction - Alber, Erdmute; Kölbl, Carlos (cultura & psyché, 2023)
This introductory paper starts by observing a worldwide demand to ‘leave illiteracy behind’. We explicate and question the spatio-temporal metaphor that implicitly underlies this idea, which is exemplified in the UNESCO Millennium Goal of ‘Education for All’. In place of a binary opposition between literacy and illiteracy or treating them as static essences, we focus on dynamic, multiple and relational processes and propose the terms ‘literacising’ and ‘illiteracising’. The notion of a multiplicity of (il)literacies is at the core of every contribution to this thematic issue. Our introduction presents and discusses the central aspects of these contributions in their own terms but also sometimes goes further. The articles focus on a multiplicity of (il)literacies in various parts of the world, including Bolivia, Benin, Zambia, Ghana, Uganda and India, that are accompanied by a series of conceptual shifts including a critique of normatively unequivocal connotations around literacy and illiteracy and an emphasis on literacies in the plural. After addressing such conceptual shifts, we also discuss the multifaceted role of new technologies, the peculiarities of ‘alternative’ writings such as weaving, possibilities of extending the paradigm of the ‘(New) Literacy Studies’, the complex relations between bureaucracies and (il)literacies and the figure of ‘literacy mediators.’ We conclude by returning to the contextuality of what is seen as ‘literacy’ or ‘illiteracy’ and the potentials and dangers of extending the concept of literacy and propose thinking more about how to make processes of illiteracising more productive.
Keywords: Education for All; Literacising and Illiteracising; Literacies in the plural; The (New) Literacy Studies; Literacy mediators